Chemical Composition Analysis and Heat Absorption Potential of Andesite Stone as Absorber Material in Thermoelectric Generators - Septiannissa Azzahra; Samsurizal; Aryana Rachmad Sulistya; Azli bin Yahya (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
The performance of thermoelectric generators is strongly influenced by heat absorption and thermal management on the hot side because these factors determine the temperature gradient and electrical energy output produced. Conventional ceramic materials commonly used as thermal media generally have high production costs and limited heat absorption capacity creating the need for alternative materials that are natural economical and sustainable. This study investigates andesite stone as a potential natural heat-absorbing material for thermoelectric generators through chemical composition analysis using the X-ray fluorescence method. The results show that the andesite sample is dominated by silica and alumina forming a stable aluminosilicate structure. Other identified compounds include iron oxide calcium oxide and magnesium oxide. Iron oxide contributes to increased radiation heat absorption through higher emissivity while calcium oxide and magnesium oxide improve crystal lattice stability and resistance to thermal shock. The very low loss on ignition value of 0.02% indicates minimal volatile compounds suggesting excellent thermal and chemical stability at high temperatures. Based on the relationship between composition and material properties the studied andesite stone is estimated to have moderate thermal conductivity and effective thermal buffering capability which are beneficial for maintaining a stable temperature gradient in thermoelectric generator systems. Overall these findings indicate that andesite stone has strong potential as a natural heat-absorbing or coating material in thermoelectric generator applications and can become a more economical and environmentally friendly alternative to conventional synthetic ceramic materials for future sustainable energy systems and broader industrial thermal applications worldwide.